Isolation Of Antiviral Compound From Cymbopogon Nardus Methanolic Fractions - Reagan Entigu, Linton @ Jerah; Samuel, Lihan; Ismail, Ahmad (International Journal of Health and Pharmaceutical Sciences, 2013)
Measles disease is an endemic disease in Malaysia and vaccine administration has been implemented in Expanded Programme on Immunization since 1982 as prevention for the infection. Cymbopogon nardus contains certain compounds such as citronella oil which is important for various cleaning and perfume products. The plant’s secondary metabolites has yet to be studied thoroughly for their bioactivities, thus this study was carried out to test C. nardus methanolic fractions for their potential as antiviral drug. The antiviral activity of each fractions or subfractions was tested at their respective concentrations of 0.5 and 0.1 lethal concentrations, LC50. The inhibition activity of fractions was determined by Vero cell viability due to the nature of measles virus to cause cell lysis. Two type of treatments to determine antiviral mechanism were used, ((C + V) + F) and ((C + F) +V). The fractions interfered with viral processes rather than provide protection to Vero cells prior to inoculation with 10 μL measles virus 1000 TCID50. Fraction C2 produced high activity compared to other fractions and was selected for subfractionation with column chromatography that yielded 9 subfractions. Active subfraction C2.1 was selected for scrap TLC to isolate the compounds. Octadecenoic acid, methyl ester a polyunsaturated fatty acid was abundantly presence in the active subfractions among 4 subfractions or compounds separated from the subfraction C2.1 with significant antiviral activity (p < 0.05) at 84.01 ± 1.1 % compared to control, ribavirin (78.16 ± 0.7 %). The results of the study suggest that octadecanoic acid, methyl ester has potential as antiviral drug candidate.